Moral, Instructional, and Transformational Leadership in High-Performing Schools: Organizational Support for Strengthening School and Student Achievement - Kartika Hudayana; Ibrahim Bafadal; Burhanuddin Burhanuddin; Adi Atmoko (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Leadership plays a crucial role in improving educational quality, particularly in high-performing schools that are expected to strengthen both school and student achievement. Previous studies have mainly examined moral, instructional, and transformational leadership separately, resulting in a limited understanding of their collective contribution to school effectiveness. Additionally, the role of perceived organizational support (POS) in enhancing leadership effectiveness remains underexplored. This study examines the influence of moral, instructional, and transformational leadership on school and student achievement, as well as the moderating role of POS. The research was conducted in high-performing private Islamic senior high schools in East Java, Indonesia, as part of the educational transformation toward Indonesia 2045. Using a quantitative explanatory design, data were collected from 250 teachers across 15 schools through structured questionnaires and analyzed using SEM-PLS. The findings reveal that all three leadership dimensions significantly contribute to strengthening school achievement and fostering a positive school climate that supports student achievement. Transformational leadership emerged as the strongest predictor, while moral leadership showed a substantial contribution to school excellence. Furthermore, POS selectively strengthened the influence of moral and transformational leadership on educational outcomes. This study highlights the importance of collective leadership capacity and organizational support in sustaining educational quality and school excellence.